2018
DOI: 10.1093/biolre/iox184
|View full text |Cite
|
Sign up to set email alerts
|

Lhx8 ablation leads to massive autophagy of mouse oocytes associated with DNA damage†

Abstract: Following proliferation of oogonia in mammals, great numbers of germ cells are discarded, primarily by apoptosis, while the remainder form primordial follicles (the ovarian reserve) that determine fertility and reproductive lifespan. More massive, rapid, and essentially total loss of oocytes, however, occurs when the transcription factor Lhx8 is ablated-though the cause and mechanism of germ cell loss from the Lhx8-/-ovaries has been unknown. We found that Lhx8−/− ovaries maintain the same number of germ cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…This indicates that there exist other mechanisms responsible for extensive oocyte degeneration and follicles formation (Greenfeld, Pepling, Babus, Furth, & Flaws, ; Perez et al, ). Our study together with others have demonstrated that autophagy‐induced PCD of oocytes may be pivotal for oocyte loss and functional follicles formation in mice without affecting meiosis because the number of oocytes recovered after inhibiting autophagy was significantly higher than that of apoptosis (Ignazio et al, ; Rodrigues et al, ; Tu et al, ). Apoptosis appears to eliminate oocytes with genetic or meiotic pairing errors, while autophagy helps oocytes to form functional follicles.…”
Section: Discussionsupporting
confidence: 66%
“…This indicates that there exist other mechanisms responsible for extensive oocyte degeneration and follicles formation (Greenfeld, Pepling, Babus, Furth, & Flaws, ; Perez et al, ). Our study together with others have demonstrated that autophagy‐induced PCD of oocytes may be pivotal for oocyte loss and functional follicles formation in mice without affecting meiosis because the number of oocytes recovered after inhibiting autophagy was significantly higher than that of apoptosis (Ignazio et al, ; Rodrigues et al, ; Tu et al, ). Apoptosis appears to eliminate oocytes with genetic or meiotic pairing errors, while autophagy helps oocytes to form functional follicles.…”
Section: Discussionsupporting
confidence: 66%
“…Samples were cut into 7 µm sections by a cryostat (Leica, Germany). Sections were stained by Heidenhain's Azan method (D’Ignazio et al, ). In order to measure the diameter and wall thickness of seminiferous tubules as well as the nucleus diameter of the spermatogonia, the sections were photographed under light microscopy (Olympus, Japan) by a camera.…”
Section: Methodsmentioning
confidence: 99%
“…Then the RNA microarray dataset from Lhx8 knockout mice was included (GSE109473). It has been reported that Lhx8 knockout leads to massive depletion of the primordial follicle and induces OR depletion in mice ( Ren et al, 2015 ; D'Ignazio et al, 2018 ). The results showed that the expression of six genes, including Lhx8 , Sohlh1 , Nobox , Stk31 , Tbpl2 , and Padi6 , was significantly reduced in ovary tissues from Lhx8 knockout mice, while no probe of Vrtn was observed ( Figure 6B ).…”
Section: Resultsmentioning
confidence: 99%